Louis-Hector de Callières, gouverneur et lieutenant général de la Nouvelle-France, 1698--1703 - Dorlot, François (University of Ottawa (Canada), 1970)
Abstract not available.
Keywords: Biography.; Canadian Studies.; Political Science, General.